Treatment of primary molar utilizing lesion sterilization and tissue repair: a case report (Research, Society and Development, 2021)
Aim: Non-instrumental endodontic therapy has stood out for being a minimal intervention approach that uses a mixture of antibiotics to disinfect the root canals. The purpose of this case report was to describe the treatment and 36-month follow-up of a deciduous necrotic molar using the modified technique of “Injury Sterilization and Tissue Repair” (LSTR). Methodology: A 5-year-old female patient sought dental care complaining of pain in the region of tooth 85 whose oral clinical examination revealed the presence of caries with pulp involvement. In the preoperative period (T1), the patient presented with fistula, abscess and edema. Endodontic treatment was performed using the LSTR technique with triple antibiotic paste. In the follow-up, due to radiographic aspects, a large interradicular lesion was observed in T1 and at the end of the follow-up (T4 / T5), complete bone regeneration was observed in the region. Conclusion: Due to the high antibacterial efficacy of the paste used, the LSTR technique showed satisfactory results in the pulpectomy of a deciduous necrotic molar. Clinical significance: This technique shows the potential to be used in cases to being performed in a shorter operative time, which can be useful in the treatment of children with negative behavior.